2011
DOI: 10.1016/s1995-7645(11)60230-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plumbagin free alcohol extract of Plumbago zeylanica Linn. root on reproductive system of female Wistar rats

Abstract: All findings suggest that the antifertility activity of extract could possibly be through the changes in the implantation site, altered hormonal levels, prolonged estrous cycle and anti-estrogenic activity. Hence, the extract possesses reversible antifertility activity without adverse toxicity in female rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 11 publications
3
12
0
1
Order By: Relevance
“…A positive correlation has been established between testosterone level and motility, density and fertilizing capacity of the spermatozoa. It has been reported that androgen binding protein and testosterone produced by the Leydig cells reaches to the epididymis through the testicular fluid and maintains the Epididymis testosterone level 119,120,121 . Since testosterone level affect the functional integrity of testis and epididymis, motility density and viability of spermatozoa suggests that Withania somnifera (W S) extract treatment might altered the functional integrity of testis and epididymis responsible to cause degenerative changes in these organs, responsible for reduction of fertility in W S treated rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive correlation has been established between testosterone level and motility, density and fertilizing capacity of the spermatozoa. It has been reported that androgen binding protein and testosterone produced by the Leydig cells reaches to the epididymis through the testicular fluid and maintains the Epididymis testosterone level 119,120,121 . Since testosterone level affect the functional integrity of testis and epididymis, motility density and viability of spermatozoa suggests that Withania somnifera (W S) extract treatment might altered the functional integrity of testis and epididymis responsible to cause degenerative changes in these organs, responsible for reduction of fertility in W S treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol is a steroid metabolite found in the cell membranes and transported in the blood plasma of animals. It is an essential structural component of mammalian cell membranes, an important component for the manufacture of bile acids, steroid hormones, and fat soluble vitamins 40,41 .The effect of W.somnifera on cholesterol is a reduction in cholesterol level of blood in diabetic W.somnifera treated group relative to diabetic control group has been observed 25 . Maytenus emargineta plant extracts also showed same effect on male albino rats 43 .…”
Section: Effect On Cholesterolmentioning
confidence: 98%
“…Hence, one-five of this dose, i.e., up to 500 mg/kg body weight, was used for antifertility investigation. Hematological and biochemical parameters were also performed before and after treatment and no significant changes were observed [12][13][14][15][16].…”
Section: Acute Oral Toxicitymentioning
confidence: 99%
“…The reduced level of hormone may also be due to inactivation of luteinization of ovarian follicles, which could be responsible for the reduction in the concentration of serum progesterone in this study [14,[22][23][24][25][26][27][28]. An elevated level of progesterone during pregnancy plays a key role in maintaining the conditions and is an important factor in the implantation process.…”
Section: Hormonal Analysismentioning
confidence: 99%
“…The number of litters was determined after the completion of one gestation period in all experimental groups. [15] The litters were allowed to grow and the growth of litters produced from the extractadministered group was compared with those of control group. The reversibility of antifertility effect of the extracts was also studied in the treated groups.…”
Section: Antifertility Studymentioning
confidence: 99%